Sustainability Policy in a New Autonomous City: Evidence of Economic Structure and Determinants from Banjar Municipality, Indonesia - Supriyadi, Agus; Wang, Tao; Safitri, Susi; Cirella, Giuseppe T; Juwita, Melda R (Indonesian Journal of Sustainability Accounting and Management, 2021)
With a governance shift in Indonesia, a heavy burden has been placed on local governments to act in their citizens’ best interests. This study generated evidence of economic structure, economic growth, and local government policies in the new autonomous city of Banjar Municipality, West Java Province, Indonesia. This study used location quotient, shift-share, and ordinary least squares regression analyses. Results reveal that from 2017 to 2019, agriculture, accommodations, business and trade, public services, and other sectors dominated the economic structure of Banjar Municipality. Notably, the Banjar city government's sustainability policy, aimed at developing local road infrastructure and protecting traditional markets, plays an essential role in maintaining the city’s economic growth. Policies oriented toward sustainability emphasize control, orderliness, and acceleration of economic activity; however, local authorities are at times faced with challenges when a transition of regional leadership occurs. This study provides critical insights that complement the theorization and evaluation of new autonomous cities' attempts to achieve community welfare.